VO2 off transient kinetics in extreme intensity swimming - Sousa, A.; Figueiredo, P.; Keskinen, K. L.; Rodriguez, F. A.; Machado, L.; Vilas-Boas, J. P.; Fernandes, R. J. (Journal of Sports Science & Medicine, 2011)
Inconsistencies about dynamic asymmetry between the on- and off- transient responses in oxygen uptake are found in the literature. Therefore, the purpose of this study was to characterize the oxygen uptake off-transient kinetics during a maximal 200-m front crawl effort, as examining the degree to which the on/off regularity of the oxygen uptake kinetics response was preserved. Eight high level male swimmers performed a 200-m front crawl at maximal speed during which oxygen uptake was directly measured through breath-by-breath oxymetry (averaged every 5 s). This apparatus was connected to the swimmer by a low hydrodynamic resistance respiratory snorkel and valve system. Results: The on- and off-transient phases were symmetrical in shape (mirror image) once they were adequately fitted by a single-exponential regression models, and no slow component for the oxygen uptake response was developed. Mean (± SD) peak oxygen uptake was 69.0 (± 6.3) mL·kg-1·min-1, significantly correlated with time constant of the off- transient period (r = 0.76, p < 0.05) but not with any of the other oxygen off-transient kinetic parameters studied. A direct relationship between time constant of the off-transient period and mean swimming speed of the 200-m (r = 0.77, p < 0.05), and with the amplitude of the fast component of the effort period (r = 0.72, p < 0.05) were observed. The mean amplitude and time constant of the off-transient period values were significantly greater than the respective on- transient. In conclusion, although an asymmetry between the on- and off kinetic parameters was verified, both the 200-m effort and the respectively recovery period were better characterized by a single exponential regression model.